Self-Annealing Behavior of Electroplated Cu in Blind-Hole Structures. Issue 13 (1st January 2019) - Yang, Cheng-Hsien; Lee, Yu-Wei; Lee, Cheng-Yu; Chang, Chih-Hao; Ho, Cheng-En
Abstract : Blind-hole (BH) metallization via Cu electrodeposition is a critical technology for printed circuit boards (PCBs) with high-density interconnections (HDIs) because it provides excellent thermal and electrical conductivity and efficient space utilization. In this study, the self-annealing behavior of electroplated Cu was in-situ characterized via ohmmeter measurements, field-emission scanning electron microscopy (FE-SEM) in combination with electron backscatter diffraction (EBSD) analysis, and time-of-flight secondary ion mass spectrometry (TOF-SIMS). A strong correlation among the electrical property transition, Cu crystallographic transition, and impurity distribution was established that supports the curvature enhanced accelerator coverage (CEAC) mechanism and advances our understanding of the Cu physical/chemical characteristics in BH structures.